Measuring entrepreneurial lecturers' competency and performance by applying a participatory knowledge management approach in the "Foreign Experts Introduction Project" in China. (5th January 2023) - Miao, Ting; Janchai, Worawit; Panyanuwat, Anurak
Enhancing lecturers' competencies must be considered by the authorities as it increases teaching performance and the quality of learning among students. However, limited studies have been concerned with measuring the lecturers' competencies, especially in the context of China. Therefore, this paper aims to examine the effects of the competency level of entrepreneurial lecturers' performance in the "Foreign Experts Introduction Project" in China. Structural equation modelling (SEM) in smart-PLS is used to confirm hypotheses about the impact of lecture competencies on lecture performance. SPSS is used for cleaning purpose of data. This study provides some insights into the specific competencies that could focus on during the "Foreign Experts Introduction Project". Results indicate that to increase the competency level of lecturers, the participatory knowledge management approach in the "Foreign Experts Introduction Project" does necessarily improve the performance of local lecturers. The study found that lecturers with communication competence have the most influence on their performance. Conversely, lecturers who do not have job competence will generate low work productivity.